Benzylation of benzene and other aromatics by benzyl chloride over mesoporous AlSBA-15 catalysts - Vinu, A.; Sawant, D. P.; Ariga, Katsuhiko; Hartmann, Martin; Halligudi, Shivappa B. (Microporous and Mesoporous Materials, 2005)
Aluminum-containing mesoporous molecular sieves AISBA-15 with different n(Si)/n(Al), ratios and AIMCM-41 have been synthesized hydrothermally and characterized in detail by physicochemical methods, viz. XRD, N(2) adsorption and (27)Al NMR spectroscopy. The low angle XRD and N2 adsorption measurements reveal that the structural order of SBA-15 was retained after the incorporation of Al. The increase of the unit cell parameter with increasing aluminum content and (27)Al MAS NMR spectroscopy confirm the incorporation of aluminum in the framework. Benzylation of benzene and substituted benzenes reaction employing benzyl chloride as the alkylating agent over AISBA-15 and AIMCM-41 have been investigated. The influence of various reaction parameters such as reaction temperature, reactant feed ratio and catalyst amount affecting the activity and selectivity of AISBA-15, have been studied. Among the mesoporous catalysts studied, AISBA-15(45), where the number in parentheses indicates the molar nsilnA, ratio, shows both high conversion and high selectivity for the benzylation of benzene. The activity of this catalyst for the benzylation of different aromatic compounds is in the following order: benzene > toluene > p-xylene > mesitylene > anisole. Kinetics of the benzene benzylation over different catalysts have also been investigated. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Alkylation; AlSBA-15; Benzylation; SBA-15

Highly active and selective AlSBA-15 catalysts for the vapor phase tert-butylation of phenol - Vinu, A.; Devassy, Biju M.; Halligudi, Shivaraj B.; Bohlmann, W.; Hartmann, Martin (Applied Catalysis A-General, 2005)
Hexagonally ordered mesoporous AISBA-15 catalysts having n(Si)/(nA]) ratios from 7 to 215 have been synthesized hydrothermally using a cheap non-ionic block copolymer as the structure-directing agent. The obtained materials were analyzed by XRD and nitrogen adsorption to determine the structural order and the textural properties. It has been observed by Al-27 MAS NMR spectroscopy that aluminum atoms are exclusively in tetrahedral coordination for all samples except AISBA-15(7), where octahedral aluminum has been detected to some extent. Temperature-programmed desorption of pyridine showed that AISBA-15(45) has a higher number of strong acid sites as compared to other mesoporous materials such as FeMCM-41, AIMCM-41 and FcAlMCM-41. The catalyst AlSBA-15(45)showed superior performance in the acid-catalyzed tertiary butylation of phenol employing tert-butanol as the alkylation agent. A high phenol conversion of 86.3% is observed for this catalyst at a reaction temperature of 150 degrees C. Over AISBA-15(45), the 4-TBP yield amounts to 40.5% and the 2,4-DTBP yield corresponds to 37.9%. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Acidity; AlSBA-15; aluminum incorporation; butylation of phenol; SBA-15

Adsorption of methanol on Si(100)/SiO(2)and mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Ravi, V.; Jacob, Nalini E.; Patil, K. R. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of methanol on SiO(100)/SiO2 substrate and mesoporous SBA-15 has been studied by using Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is employed to study the adsorption kinetics of methanol on SiO(100)/SiO2 and thermal stability of adlayer. Thermogravimetric (TGA) technique is used to understand the thermal behavior of methanol layer on SBA-15. Adsorption kinetics fit fairly well with Langmuir isotherms giving adsorption rate constant, k(a) = 0.0021 W s(-1). FTIR results show formation of methoxy silicon (SiOCHA silicon polyhydride (SiH2), carboxylate, molecular water and hydroxyl groups on Si(100)/SiO2 surface and only methoxy silicon on SBA-15. XPS results confirm methanol adsorption and support FTIR results. The methanol adlayers are found to be thermally stable up to a temperature of similar to 262 degrees C on both Si(100)/SiO2 and SBA-15 and decompose between 262 and 450 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; desorption; kinetics; Methanol; SBA-15; Si(100)/SiO2; thermal stability

Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability

Adsorption of octadecyltrichlorosilane on Si(100)/SiO2 and SBA-15 - Mirji, S. A. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on Si(100)/SiO2 substrate and mesoporous SBA-15 has been studied by energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is used to study the adsorption kinetics of OTS on Si(100)/SiO2 and thermal stability of adsorbed OTS layer. Thermogravirnetric (TGA) technique is employed to understand the thermal behavior of OTS adlayer on SBA-15. Langmuir isotherms fit very well with OTS adsorption kinetics data on Si(100)/SiO2 and furnish adsorption rate constant, k(a) = 236 M-1 s(-1), desorption rateconstant, k(d) = 0.0082s(-1) and Gibbs free energy of adsorption, Delta G(ads) = -6.28 kcal mol(-1). EDAX and XPS results both show increased carbon content due to OTS adsorption and decreased oxygen and silicon content due to screening of these elements by OTS adlayer. FTIR data shows methylene (-CH2) and methyl (-CH3) stretching bands, in close agreement with reported data. The OTS layers are found to be thermally. stable up to a temperature of approximate to 260 degrees C on both Si(100)/SiO2 and SBA-15. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Gibbs free energy; OTS; SBA-15; Self-assembly; Si(100)/SiO2; thermal stability

Adsorption of methanol on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B. (Materials Letter, 2007)
The adsorption of methanol onmesoporous SBA-15 has been studiedbyrising Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoclectrom spectroscopy (XPS) and tbennogravimettic analysis (TGA). The BET surface area analysis shows decreases of the surface area from 387 to 383 m(2)/g, pore volume from 0.88 to 0.81 cm(3)/g and pore diameter from 9.07 to 8.4 mm after methanol adsorption. The appearance of strong IR bands at 2862 and 2964cm(-1) due to methyl (-CH3) symmetric and asymmetric stretching demonstrate the presence of methanol and evidence of successful methanol adsorption. XPS results show increase of carbon and oxygen content on the surface of SBA-15. Thermogravirriettic analysis shows that the methanol adsorbed on SBA-15 is stable up to a temperature of 265 degrees C and that the methanol adlayers decompose between 265 and 588 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Electron microscopy; Methanol; SBA-15; Surfaces; thermal stability

Catalytic performances of silicotungstic acid/zirconia supported SBA-15 in an esterification of benzyl alcohol with acetic acid - Sawant, Dhanashri P.; Vinu, A.; Justus, Josena; Srinivasu, P.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Liquid phase esterification of benzyl alcohol (BA) to benzyl acetate (Peach fragrance) with an acetic acid (AA) has been investigated with 12-silicotungstic acid supported on zirconia embedded inside SBA-15 (STA/ZrO2/SBA- 15) as the catalyst. Catalysts were unambiguously characterized by XRD, N-2 adsorption-desorption, FF-IR pyridine adsorption techniques and the total amount of acidity of different STA loaded catalysts was estimated by TPD of NH3. The optimization of reaction conditions of an esterification of BA with AA was performed with 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K by varying catalyst concentration (1-10 wt.% of reaction mixture); temperature, 353-383 K and AA:BA molar ratio as 0.5-3. The 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K was found to have the highest acidity and more active in the reaction. Under the optimized reaction conditions, the 15 wt.% STA/22.4 wt.%ZrO2/SBA-15 calcined at 1123 K gave 59% BA conversion with selectivity for benzyl acetate as high as 96% within 2 h of reaction time. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: 12-silicotungstic acid; Benzyl acetate; Benzyl alcohol; Esterification; SBA-15

Effect of pretreatment conditions on the catalytic activity of nano-sized TPA/ZrO2 dispersed in SBA-15 channels in acetylation reactions - Sawant, Dhanashri P.; Hartmann, Martin; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2007)
Acetylation of an aromatic compounds such as veratrole (1,2-dimethoxybenzene), anisole, thioanisole, isobutyl benzene and 2-methoxynaphthalene with acetic anhydride has been investigated over a nano-sized 12-tungstophosphoric acid (TPA)/22.4 wt.%ZrO2/SBA- 15 catalysts in the liquid phase conditions. Catalysts with different (%) TPA and zirconia loadings calcined at different temperatures were prepared by wet-impregnation and characterized by XRD, N-2 adsorption-desorption, FT-Rarnan, X-ray photoelectron spectroscopy (XPS). The acidic behavior of the catalyst was studied by TPD of ammonia and FT-IR pyridine adsorption. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/SBA- 15 calcined at 1123 K had the highest acidity and was the most active catalyst in veratrole acetylation with acetic anhydride. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: acetylation; SBA-15; TPA/ZrO2; veratrole; wet-impregnation

Immobilization of invertase on functionalized mesoporous silica and properties of the immobilized biocatalyst - Prabhune, Asmita Ashutosh; Sulabha, Karandikar; Archana, Pundle; Shilpa, Deshpande; Sanjeevani, Pardhy (Research Journal of Biotechnology, 2007)
Invertase, which catalyses the hydrolysis of sucrose, is one of the simplest commercial carbohydrases and is used for the production of invert syrup (mixture of glucose and fructose). Fructose is the sweetest natural sugar having beneficial medicinal effects and is emerging as an alternative sweetener to sucrose in the pharmaceutical industry. beta fructofuranosidase (E C 3.2.1.26) purified from Kluyveromyces marxianus NCYC 2675, a thermotolerant yeast, was immobilized on functionalized mesoporous silica SBA- 15. Attempts were made to immobilize invertase on functionalized silicalite and cross linked with glutaraldehyde so as to obtain a highly active and stable immobilized enzyme preparation suitable for commercial exploitation. Cross linked enzyme silica complex as well as enzyme silica complex showed very good temperature and pH stability. Extrudates of the mesoporous silica also showed similar results. Bound enzyme showed excellent stability to repeated use and retained 90% of its initial activity after ten cycles of reuse in batch mode.
Keywords: beta fructofuranosidase; extrudates; functionalized mesoporous silica; Invert syrup; invertase; SBA-15

Structural features of Penicillin acylase adsorption on APTES functionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
The immobilization of Penicillin acylase (PGA) enzyme (which belongs to the Ntn hydrolase super family) into the amino-functionalized SBA-15 mesoporous molecular sieve is carried out to see the effect of silica as a host matrix on the enzyme kinetics. Physicochemical characterization by nitrogen adsorption, powder XRD and TEM methods indicate that the characteristic hexagonal features and the original pore structure of the parent SBA-15 is retained even after the incorporation of PGA. The adsorption of PGA on SBA15 shows a dependence on the pore volume and the composition of the adsorbent. The maximum loading of the enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The trapped enzyme is more stable than the soluble form to temperature and pH environments and retained 73% of its activity after immobilization. This enhanced stability is attributed to the protective nature of the cage itself and to the rigidity of the SiO(2) matrix, which reduces the freedom of peptide-chain refolding of molecular motions that occur in denaturation processes. The strength of binding is very strong; however, the activity of the immobilized enzyme is then simply restored with very little leakage of enzyme from the support. An important feature of the immobilized PGA enzyme is the excellent reusability without significant loss in activity, which indicates potentially exciting industrial/biomedical application of this support. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Penicillin G acylase; PGA immobilized SBA-15; pH and temperatures stability; SBA-15

Mesoporous silica immobilized cobalt complex: an efficient catalyst for epoxides ring opening by aromatic amines under ambient conditions - Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shivaraj B. (Catalysis Communications, 2009)
{Cobalt complex, CobpbH(2)Cl(2)2H(2)O [where
Keywords: beta-Amino alcohols; CobpbH(2)Cl(2)2H(2)O complex; Epoxide ring opening; Immobilization; SBA-15

Ru(II)-Chiral (1R,2S)-(+)-cis-1-amino-2-indanol immobilized over SBA-15 for asymmetric transfer hydrogenation reaction of prochiral ketones - Parambadath, Surendran; Singh, A. P. (Catalysis Today, 2009)
Mesoporous SBA-15 (Santa Barbara University at California) has been synthesized and functionalized with (4-chloromethyl)phenyltriethoxysilane, there after the surface silanols groups were passivated by dimethoxydimethylsilane (MeO(2)Me(2)Si) [Bz-SBA-15]. Further (1R,2S)-(+)-cis-1-amino-2-indanol [AIL] has been immobilized over functionalized SBA-15 (BzAIL-SBA-15). The heterogeneous catalysts were synthesized by complexation of BzAIL-SBA-15 by [RuCl(2)(benzene)](2) and [RuCl(2)(p-cymene)](2) in 2-propanol at reflux condition designated as Ru-Bn-BzAIL-SBA-15 (Ru-1) and Ru-Cy-BzAIL-SBA-15 (Ru-2). The synthesized materials have been characterized by small angle X-ray diffraction spectroscopy (SAXS), N(2) adsorption-desorption isotherms, Fourier Transformed-Infra-red (FT-IR) spectroscopy, Transmission Electron Microscopy (TEM), intensively Coupled plasma atomic emission spectroscopy (ICP-AES), Diffuse reflectance UV-vis and (13)C CP MAS NMR analysis. Further the synthesized and characterized materials (Ru-1 and Ru-2) have been successfully applied in the asymmetric transfer hydrogenation (ATH) reaction of simple prochiral ketones, which gave a yield of 56% and 18% and enantiomeric excess (ee) values of 62% and 77% for Ru-1 and Ru-2, respectively, after 1 h for acetophenone. The reusability studies showed approximately the same enantiomeric excess value at lower conversions. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: (1R; 2S)-(+)-Cis-1-amino-2-indanol; Asymmetric transfer hydrogenation; Chiral amino alcohols; Mesoporous molecular sieve; Prochiral ketones; SBA-15

Regiospecific oxyhalogenation of aromatics over SBA-15-supported nanoparticle group IV-VI metal oxides - Saikia, Lakshi; Rajesh, M.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2010)
TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 exhibit efficient catalytic activity for oxyhalogenation of aromatics with the H(2)O(2)-halide ion system. Unlike the hitherto known solid catalysts, these reusable catalysts yield the para-halogenated product with 100% selectivity at 298 K and moderate acidic pH (3-5). The catalytic activity was enhanced by five orders of magnitude when supported on SBA-15.
Keywords: Haloperoxidase activity; Ordered mesoporous silica; Oxyhalogenation of aromatics; SBA-15; Supported metal oxides

Effect of method of preparation on hydrodesulphurization activity of Co- or Ni-promoted MoS2/SBA-15 catalysts - Garg, Shelu; Soni, Kapil; Prasad, V. V. D. N.; Kumar, Manoj; Bhaskar, Thallada; Gupta, J. K.; Dhar, G. Murali; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2014)
Ordered mesoporous material SBA-15 was synthesized and used as a support for the preparation of molybdenum sulphide catalysts through precipitation from homogeneous solution (PFHS) technique with the Mo content varying from 2-12 wt%. The prepared catalysts were evaluated for thiophene hydrodesulphurizadon catalytic activities at 400 degrees C. Catalysts prepared through PFHS method resulted in highly dispersed MoS2 catalysts, which were inferred from powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), low temperature oxygen chemisorptions (LTOC) and BET surface area analysis. The relationship between XPS intensity ratio, oxygen chemisorption and catalytic activities is discussed in terms of highly dispersed nano particles of MoS2 and its consequence in accommodating more promoted atoms at the edge sites.
Keywords: HDS; MoS2; PFHS method; promotional effects; SBA-15

Immobilization of bile salt hydrolase enzyme on mesoporous SBA-15 for co-precipitation of cholesterol - Bhange, Pallavi; Sridevi, N.; Bhange, Deu S.; Prabhune, Asmita; Ramaswamy, Veda (International Journal of Biological Macromolecules, 2014)
We describe herein a simple and effective strategy for immobilization of bile salt hydrolase enzyme by grafting glutaraldehyde groups inside channels of APTES functionalized SBA-15. The increase in glutaraldehyde concentration prevents leakage of enzyme but showed a steep decrease in enzyme activity in the immobilized matrix. So the degree of cross-linking should be the minimum possible to ensure sufficient stability without loss of activity. Cross-linking carried out with 0.1% glutaraldehyde concentration showed the highest activity, so this was used in all further experiments. Physico-chemical characterizations of the immobilized enzyme were carried out by XRD, N-2 adsorption, TEM, FUR and Si-29 CP-MAS NMR techniques. Immobilized BSH exhibits enhanced stability over a wide pH (3-11) and temperature range (40-80 degrees C) and retains an activity even after recycling experiments and six months of storage. From our in vivo research experiment toward co-precipitation of cholesterol, we have shown that immobilized BSH enzyme may be the promising catalyst for the reduction of serum cholesterol levels in our preliminary investigation. Enhancement in pH stability at the extreme side of pH may favor the use of immobilized BSH enzyme for drug delivery purpose to with stand extreme pH conditions in the gastrointestinal conditions. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bile salt hydrolase; Co-precipitation of cholesterol; SBA-15

Highly stable In-SBA-15 catalyst for vapor phase Beckmann rearrangement reaction - Kumar, Rawesh; Shah, Sneha; Bahadur, Jitendra; Melnichenko, Yuri B.; Sen, Debasis; Mazumder, S.; Vinod, Chathakudath P.; Chowdhury, Biswajit (Microporous and Mesoporous Materials, 2016)
The Indium doped SBA-15 material was prepared by sol-gel method and tested for vapor phase Beckman rearrangement reaction. Among three indium loading, In/Si ratio of 2/100 was found as an optimum composition in terms of caprolactam selectivity (100%) and cyclohexanone oxime conversion (100%). The catalysts were characterized by N-2 adsorption, small-angle X-rays/neutron scattering (SAXS/SANS), XRD, FESEM, HRTEM, EDX, UV, FTIR and NH3-TPD techniques. In-situ SANS experiment was performed on the adsorption of CO2 to detect the micropores in the mesopore wall. All catalysts samples have highly ordered hexagonal structure with well dispersed indium in the silica matrix. The fine tuning of weak and strong acid sites were found in indium doped SBA-15 (In/Si = 2/100) catalyst. The same catalyst showed optimum catalytic performance, high space time yield 114.4 mol/h/g(cat) and high stability till 6 h of reaction without deactivation. The micro-kinetic analysis showed that there were no external and internal diffusion limitations in the SBA-15 catalyst. The reaction mechanism of Beckmann rearrangement over In-SBA-15 has been elucidated. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: e-Caprolactam; In-situ SANS; indium; SAXS; SBA-15

PD@SBA-15 Nanocomposite catalyst: synthesis and efficient solvent-free semihydrogenation of phenylacetylene under mild conditions - Bhuyan, Diganta; Selvaraj, Kaliaperumal; Saikia, Lakshi (Microporous and Mesoporous Materials, 2017)
Pd-0 nanoparticles (NPs) have been fabricated on SBA-15 using a facile, rapid and highly reproducible microwave-assisted reduction by solvent method. The as-synthesized Pd@SBA-15 nanocomposite was well characterized using low angle and wide angle XRD, TEM, FE-SEM, N-2 adsorption-desorption isotherm, FTIR, XPS etc. The Pd@SBA-15 nanocomposite act as an active, recyclable heterogeneous catalyst for semihydrogenation of phenylacetylene under solvent-free mild reaction conditions (303 K, atmospheric H-2). A maximum of 94.4% phenylacetylene conversion was achieved with very high selectivity for styrene (95.5%). Moreover, the used catalyst was recovered by centrifugation and reused up to four times without significant loss in their catalytic activity. This optimized reaction protocol for phenylacetylene was also well performed in case of various other alkynes with similar or better performance. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Pd-0 nanoparticles; Phenylacetylene; SBA-15; Semihydrogenation; Solvent-free

Synthesis and characterization of D-2PA-Pd(II)@SBA-15 catalyst via ``click chemistry'': highly active catalyst for Suzuki coupling reactions - Pathak, Aruna; Singh, A. P. (Journal of Porous Materials, 2017)
Copper catalysed cycloaddition reaction between azide and terminal alkyne, called as ``click reaction'', was found to be modular approach for the synthesis of facile, highly efficient and recoverable D-2PA-Pd(II)@SBA-15 catalyst. In efforts to synthesize the catalyst, the cycloaddition reaction between azido-functionalized mesoporous SBA-15 and N,N-dimethyl-2-propynylamine (D-2PA) has been carried out, followed by the complexation with PdCl2. To analyze physiochemical properties of synthesized materials, various characterization techniques such as CHN elemental analysis, X-ray diffraction, solid state C-13 and Si-29 NMR spectra, FT-IR, XPS, SEM, TEM and N-2 sorption analysis, TGA and DTA, UV-Vis spectroscopy have been carried out. The synthesized catalyst, D-2PA-Pd(II)@SBA-15, exhibited excellent catalytic activities with good product yield and high TON towards Suzuki coupling reaction of various aryl halides with phenylboronic acid. The effect of solvent, base and temperature on coupling reactions has also been described. The developed protocol offers recyclability of catalyst for multiple (four) times without any appreciable loss in stability and catalytic reactivity.
Keywords: Click reaction; Cycloaddition; mesoporous materials; SBA-15; Suzuki coupling

Synthesis of diesel additives from fructose over PWA/SBA-15 catalyst - Patil, Chetana R. (Fuel, 2018)
A series of composites of phosphotungstic acid (PWA) H3PW12O40 with SBA-15 were prepared by varying PWA amount from 5% to 30% by one-step sol-gel hydrothermal as well as by impregnation methods. Successful incorporation of PWA into the SBA-15 framework by sol-gel method was confirmed by 31P NMR in which a shifting of the peak due to tetrahedral ‘P’ atom of PWA from −14.32 and −14.49 ppm was observed. The composites exhibited both Brønsted and Lewis acidity, large and well distributed three dimensional interconnected pores with high surface areas exhibiting excellent activity for one pot synthesis of 5-(hydroxymethyl) furfural (5-HMF) and 5-(ethoxymethyl) furfural (EMF) from fructose. The minimum loading of 5% of PWA in SBA-15, gave 78% fructose conversion with the highest yield of 70% towards 5-HMF. Increase in PWA loading up to 20% resulted in the enhanced fructose conversion of 95% accompanied by further etherification of 5-HMF to 67 and 12% yield towards EMF and ethyl levulinate (EL), respectively. Increasing the % of PWA in SBA-15 matrix resulted in increase in the acidity of the composites giving the yield trend as 5-HMF < EMF < EL. Catalyst prepared by sol-gel method showed excellent recyclability up to 3 reuses
Keywords: 5-(Ethoxymethyl) furfural; 5-(Hydroxymethyl) furfural; Phosphotungstic acid; SBA-15

Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms

C-O hydrogenolysis of C3-C4 polyols selectively to terminal diols over Pt/W/SBA-15 catalysts - Bhowmik, Susmita; Enjamuri, Nagasuresh; Marimuthu, Banu; Darbha, Srinivas (Catalysts, 2022)
Pt/W/SBA-15 catalysts (with Pt-loading = 0.5-4 wt% and W-loading = 1 wt%) prepared by the sequential impregnation method were evaluated for selective C-O cleavage of erythritol and glycerol in an aqueous medium. The Pt and W particles dispersed on SBA-15 approached close proximity at higher Pt loadings and afforded synergistic enhancement in C-O hydrogenolysis activity/selectivity. 1,4-Butanediol yields of 30.9% (at 190 degrees C, 50 bar H-2 and 24 h) and 1,3-propanediol yields of 34.4% (at 190 degrees C, 50 bar H-2 and 12 h of reaction) were obtained over these catalysts. Pt nanoparticles (facilitating dissociative H-2 adsorption and spillover) and W (present as acidic oligomeric WOx species; activating and coordinating the polyol via 1 degrees-OH group) worked in tandem for the selective hydrogenolysis of polyols yielding terminal diols of industrial demand.
Keywords: diol; Erythritol; Glycerol; Hydrodeoxygenation; Pt; SBA-15; W

Comparative investigation on the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose - Manikandan, Marimuthu; Arjunan, Ayyappan; Prabu, Marimuthu; Raja, Thirumalaiswamy; Sangeetha, Palanivelu (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Hydrotalcites (HT) have a broad spectrum of applications as prosperous heterogeneous catalysts for diverse chemical transformations. The catalytic activity of HT-based materials can be tailored by introducing siliceous material into the internal or external framework. The surface modification of the HT framework with silica mesostructures leads to the formation of versatile Lewis base, Bronsted base and redox catalytic active sites. This work presents the comparative evaluation of the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose using 1-butanol as a solvent. The composites with different external morphology were prepared by a modified template-assisted hydrothermal method, using different HT to SBA-15 proportions. The textural and morphological characterization results conferred the efficiency of the employed post-synthetic intercalation strategy to achieve the successful formation of HT/SBA-15 and SBA-15/HT composites. With optimal HT loading and surface basicity, the HTS-3 composite demonstrated the highest catalytic performance, resulting in good glucose conversions (54 %) with improved selectivity (>83 %). The observed high reactivity could be mainly attributed to the extensive dispersion of HT particles on the SBA-15 component, which contributes to a significant increase in textural properties and surface basicity. Furthermore, special attention is devoted to addressing such reactivity phenomena as active site selectivity, catalyst multifunctionality and multisite reactivity commonly encountered in mesoporous catalysis.
Keywords: composites; glucose; hydrotalcite; isomerization; SBA-15

Ultra-small Pd nanoparticles on SBA-15: an efficient catalyst for one-pot reductive alkylation of nitrobenzene with size-dependent activity - Soni, Yogita; Philip, Milda C.; Vinod, Chathakudath P. (Topics in Catalysis, 2025)
One-pot reductive alkylation of nitrobenzene with alcohol is an important organic synthesis reaction to form 2 degrees amines. In the present work, we have demonstrated that Pd/SBA-15 can be an effective catalytic system for this reaction. We have designed ultra-small Pd nanoparticles supported on SBA-15 for the synthesis of secondary amine, N-ethylaniline, through one-pot reductive alkylation of nitrobenzene with ethanol under ambient conditions. Ethanol functions both as the alkylating agent and the solvent in this process. The reaction is driven by the simultaneous hydrogenation of nitrobenzene to aniline, dehydrogenation of ethanol to aldehyde, and condensation of aniline and acetaldehyde to form N-ethylaniline. The size of the Pd nanoparticles plays a decisive role in the product selectivity. The undercoordinated sites present on ultra-small Pd NPs can facilitate ethanol dehydrogenation to acetaldehyde, thereby enhancing the selectivity towards N-ethylaniline compared to larger Pd nanoparticles. We have also studied the effect of different mesoporous supports such as SBA-15, MCM-41, and KIT-6 on the N-ethylaniline selectivity and found that SBA-15 was most selective. We have demonstrated that by carefully designing the catalyst such as controlling the Pd NPs size to obtain the maximum quantity of undercoordinated sites and choosing suitable support, the aliphatic alcohols can also be used for reductive alkylation of nitrobenzene in one-pot with optimum yields of N-alkylaniline.
Keywords: KIT-6; MCM-41; Modified deposition precipitation; nitrobenzene; Pd nanoparticles; Reductive alkylation; SBA-15; secondary amines; Undercoordinated Pd sites